Landasan Keimanan dan Keyakinan Muslim - Bella Adelia; Febri Darmayanti; Puan Nayla Azzahra; Shania Septi Maharani (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The background of this study, belief in Islam is the foundation that determines a Muslim's beliefs and direction in life. Belief includes faith in Allah SWT, angels, His books, His messengers, the Day of Judgment, and destiny. This article aims to explain the concept of belief comprehensively, including its central role in shaping a Muslim's beliefs and obedience. This research method uses a basic theory method that uses data from materials that are library research, where the author reads and studies books or literature related to the problem being studied. Aqidah functions not only as a basis for theological beliefs, but also as a moral and ethical guide in everyday life. The resuly show that belief functions not only as a basis for theological belief, but also as a moral and ethical guide in daily life. A correct understanding of belief will lead a person to sincere obedience, devotion to Allah, and harmonious relationships with fellow human beings. This article also discusses how a strong belief becomes a driving force in living a meaningful spiritual life, and strengthens faith as a foundation in facing life's challenges.